2020
DOI: 10.3390/f11101068
|View full text |Cite
|
Sign up to set email alerts
|

To Plant or Not to Plant, That Is the Question: Reforestation vs. Natural Regeneration of Hurricane-Disturbed Mangrove Forests in Guanaja (Honduras)

Abstract: Background and Objectives: Mangrove forests offer many essential ecosystem services, including the protection of (sub)tropical coastlines, their inhabitants, and the infrastructure from severe storms and tsunamis. However, mangroves themselves suffer severely from such phenomena. After such events, reforestation efforts are widely undertaken to facilitate the recovery of the mangroves. Many of these laborious activities, however, fail for a number of reasons. Material and Methods: In October 1998, the Honduran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…This outcome has indeed been observed in various studies (e.g. Barnuevo et al, 2017;Fickert, 2020;Proisy et al, 2018), as well as behind the breakwater in Demak (Figure 9). It should be noted that in carbonate systems, Rhizophora species have been observed as pioneers of the coastal zone [e.g.…”
Section: Q3 Emr-dams: Can Emr-dams Induce Natural Mangrove Recovery A...supporting
confidence: 80%
See 1 more Smart Citation
“…This outcome has indeed been observed in various studies (e.g. Barnuevo et al, 2017;Fickert, 2020;Proisy et al, 2018), as well as behind the breakwater in Demak (Figure 9). It should be noted that in carbonate systems, Rhizophora species have been observed as pioneers of the coastal zone [e.g.…”
Section: Q3 Emr-dams: Can Emr-dams Induce Natural Mangrove Recovery A...supporting
confidence: 80%
“…minerogenic versus organogenic soil (Worthington et al, 2020)], when selecting an appropriate pioneer species. The presence of a few fruiting pioneers can reportedly revegetate a site more efficiently than a planting effort with better surviving, but slower growing species (Fickert, 2020). Although we were not able to include formerly native pioneers such as Sonneratia alba and Aegialitis annulata (Balun, 2011;Ilman et al, 2016), our Q4 experiment indeed demonstrated that planting with pioneers can quickly lead to the presence of a few reproductive young trees.…”
Section: Q3 Emr-dams: Can Emr-dams Induce Natural Mangrove Recovery A...mentioning
confidence: 81%
“…In many areas in the world, degraded mangrove forests are able to regenerate naturally. Comparison between natural mangrove regeneration and human-assisted regeneration after Hurricane Mitch in the Gulf of Honduras, Guanaja did not show a significant difference in the success of mangrove replanting (Fickert 2020). A total of 23 species of mangrove were recorded and they had good ability in terms of natural regeneration in several mangrove forests affected by the tsunami, including in the North Coast of Aceh, the East coast of Aceh, the West coast of Aceh and the coast of Peninsular Malaysia (Onrizal et al 2017).…”
Section: Seedling Structure and Species Compositionmentioning
confidence: 90%
“…Yet another radical re-imagination of ecosystem governance could involve allowing natural mangrove regeneration in the cyclone and flood affected regions as opposed to restorative mangrove plantation that constitutes a major part of institutional conservation governance across the Sundarbans. Natural regeneration is much more successful that plantations which are labour intensive and expensive, shows recent studies (Fickert 2020;Ellison et al 2020;Lee et al 2019, Kodikara et al 2017Iftekhar 2008;Primavera and Esteban 2008;Bosire et al 2008).…”
Section: Cultural Preservation As a Tool Of Conservation Governancementioning
confidence: 99%